1991
DOI: 10.1002/art.1780341021
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of Nonsteroidal Antiinflammatory Drugs on Proteoglycanase and Collagenase Activity in Human Osteoarthritic Cartilage

Abstract: The effects of several nonsteroidal antiinflammatory drugs, used at concentrations achievable in synovial fluid, on human osteoarthritic (OA) cartilage metalloprotease activity in vitro was studied. Acetaminophen and ketoprofen had no effect; sodium salicylate, indomethacin, and diclofenac slightly decreased proteoglycanase activity. Piroxicam and tenoxicam suppressed proteoglycanase activity by 48.2% and 68.3%, respectively, and suppressed collagenase activity by 19.1 % and 36.8%, respectively. Use of these N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 9 publications
2
14
1
Order By: Relevance
“…The reduction in the net loss of PG produced by tenoxicam is quite consistent with a recent report (Vignon et al, 1992) showing that the proteoglycanase activity present in the cartilage of human OA femoral heads sampled at the time of total hip replacement was markedly reduced in the presence of this NSAID at a concentration of 4pgml-'. It remains to determine whether this suppressive effect of tenoxicam on the loss of PGs is due either to an inhibition of the production of superoxide anions (Minta & Williams, 1985), or to a reduction in the synthesis and/or activation of proteolytic enzymes or to a stimulation of the synthesis and secretion of tissue inhibitors of proteolytic enzymes (Dean, 1991).…”
Section: Discussionsupporting
confidence: 90%
“…The reduction in the net loss of PG produced by tenoxicam is quite consistent with a recent report (Vignon et al, 1992) showing that the proteoglycanase activity present in the cartilage of human OA femoral heads sampled at the time of total hip replacement was markedly reduced in the presence of this NSAID at a concentration of 4pgml-'. It remains to determine whether this suppressive effect of tenoxicam on the loss of PGs is due either to an inhibition of the production of superoxide anions (Minta & Williams, 1985), or to a reduction in the synthesis and/or activation of proteolytic enzymes or to a stimulation of the synthesis and secretion of tissue inhibitors of proteolytic enzymes (Dean, 1991).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to other NSAIDs, tenoxicam has a chondroprotective effect in human cartilage in vitro and may have beneficial effects. 27 The present study demonstrated considerable benefits with ia tenoxicam compared with the same dose administered iv in patients undergoing day case knee arthroscopy. The cost of 20 mg tenoxicam was $2.23 and was the same in both arms of the study as the same formulary was employed.…”
Section: Discussionmentioning
confidence: 54%
“…Until now, only 2 studies have investigated the influence of diclofenac on the cartilage metabolism of the knee, and both demonstrated that diclofenac did not induce any degenerative processes (in an animal and an in vitro study) (23, 24). However, in a study by Vignon et al (25), a slightly decreased proteoglycanase activity was observed in human OA cartilage of the hip. However, those studies did not investigate the influence of diclofenac on cartilage metabolism of the hip or the knee joint simultaneously, and therefore it remains unclear how diclofenac acts on the knee or the hip joint.…”
Section: Discussionmentioning
confidence: 86%